Designing Liquid Metal Interfaces to Enable Next Generation Flexible and Reconfigurable Electronics. Issue 15 (22nd May 2017) - Ilyas, Nahid; Cook, Alexander; Tabor, Christopher E.
Abstract : Gallium liquid metal alloys are room temperature fluidic conductors that are used to create a variety of paradigm shifting concepts in stretchable and reconfigurable electronics. A viscoelastic solid oxide skin encases the bulk liquid metal alloy which allows remarkably unprecedented 3D fluidic structures to be constructed. This oxide also has detrimental effects to fluidic behavior in microchannels because it adheres to the channel walls. The work mitigates these detrimental effects in flow behavior through surface modification of the gallium oxide with phosphonic acids to control interfacial chemistry. This results in no adhesion between the gallium surface oxide and the underlying substrates and no alloying with metal electrodes, two pervasive problems in the field. In addition to control over the flow properties of the metal alloy with the oxide intact, phosphonic acid modification allows tunability of the work function and surface oxide thickness. Abstract : A novel approach to controlling the surface of gallium liquid metal alloys through organic ligands which modify the native oxide is presented. Modification of the liquid metal's surface energy (illustrated via a change in water contact angle in the figure), work function, and reduced chemical alloying with solid metal electrodes is demonstrated.